Creativity towards Design Based Learning in STEM Education - Nugroho, Oktian Fajar; Permanasari, Anna; Firman, Harry; Riandi, Riandi (Universitas Sebelas Maret, 2021)
Creativity is a key component in the last century skills and has been highlighted in curricular research globally especially in Indonesia. This research therefore aimed at analyzing and identifying perspectives of creativity by pre-service teachers when a likely solution step was generated in the DBL. Three separate design based learning activities were undertaken by 13 female and 11 male pre-service teachers. Two separate methods have been used for analysis of data gathered from pre-service teachers’ writings and drawings, half-structured interviews, and field notes. In quantitative study of pre-service teachers' works and in exploring the notions of creativity, fluency, flexibility, and originality. In this study descriptive analysis was used. In semi-structured interviews and field notes the findings of the descriptive analysis included quality analyses. Description analysis showed the highest showed in creativity and flexibility, but the lowest was originality. The findings of content analysis further showed a variety of factors influencing the uniqueness of pre-service teachers ideas including exposure of people to ideas, knowledge of design based learning and the prototyping of pre-service teachers' ideas. The study results might enhance the usage of DBL to help educators and researchers understand the strengths and limits of their pupils through the creativity and STEM education.